2016
DOI: 10.3855/jidc.7665
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge, perceptions, and attitudes towards HIV/AIDS in Bahrain: A cross-sectional study

Abstract: Introduction: HIV/AIDS is one of the major health problems worldwide. Despite the low prevalence of HIV in Bahrain, educational and awareness programs remain highly important in controlling and preventing the spread of the disease. This study aimed to assess the public's knowledge, risk perceptions, and attitudes towards HIV/AIDS in Bahrain. Methodology: A self-administered questionnaire-based survey was administered to and completed by 1,038 Bahraini adults. Results: Although the average general awareness amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…However, misconceptions about transmission were observed among a large proportion of women; such as the belief that HIV can be transmitted by mosquito bites, sharing a meal with an infected person, and shaking hands. Similar misconceptions have been reported in other studies [6,11,15,16]. These findings suggest the need to strengthen educational interventions, especially by health workers for women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, misconceptions about transmission were observed among a large proportion of women; such as the belief that HIV can be transmitted by mosquito bites, sharing a meal with an infected person, and shaking hands. Similar misconceptions have been reported in other studies [6,11,15,16]. These findings suggest the need to strengthen educational interventions, especially by health workers for women.…”
Section: Discussionsupporting
confidence: 89%
“…However, accepting attitudes were still uncommon, and attitudes should be a topic of particular attention in future educational interventions. Similar results have been reported in previous studies in Iran [11], Bolivia [18], Bahrain [6], and the United Arab Emirates [19]. According to UNAIDS, negative attitudes are common all over the world [8], and are one of the main obstacles in the fight against HIV/AIDS [17].…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were found to be reported in Sri Lanka. However, Janahi and colleagues in their findings reported that more than half of the adult participants (n = 1,630) in Bahrain would avoid sitting near, hugging or even shaking HIV infected people's hand [110][111][112].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found to be reported in Sri Lanka. However, Janahi and colleagues in their findings reported that more than half of the adult participants (n=1,630) in Bahrain would avoid sitting near, hugging or even shaking HIV infected people hands [110–112] .…”
Section: Discussionmentioning
confidence: 99%